Knowledge construction using web-based constructivist approach - Mohd Hafiz Yusoff
Although web technology is widely used in today’s classrooms, educationists are still unsure of its capacity to generate meaningful learning. As the numbers of web-based learning (WBL) materials keep increasing tremendously, more students will rely on such resources in their learning process.